Comme Dieu et comme Rien. Variations sur le nom de khôra - Cohen-Levinas, Danielle (Bollettino Filosofico, 2018)
Why Jacques Derrida measures himself against the apophasis of a discourse whose last arrival point is called God? Deconstruction of the undeconstructible name, Derrida devotes to khôra several reflections, and in particular he devotes to the theme a book. The alterity that inhabits the experience of the name, does it because it designates not the name itself but the other, that Lévinas calls the “third”. Derrida examines the tropic and the anachronism of the name khôra and he puts it “beyond its name” as anachrony of being, because it precedes the actuality itself of being by going beyond the distinction between intelligible and sensible.